2018
DOI: 10.1007/s00192-018-3767-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary microbes and postoperative urinary tract infection risk in urogynecologic surgical patients

Abstract: OBJECTIVES: Women have a 20% risk of developing a urinary tract infection (UTI) following urogynecologic surgery. This study assessed the association of post-operative UTI with bacteria in pre-operative samples of catheterized urine. METHODS: Immediately before surgery, vaginal swabs, perineal swabs and catheterized urine samples were collected and the V4 region of the 16S rRNA gene was sequenced. The cohort was dichotomized in two ways: 1) standard day-of-surgery urine culture result (positive/negative) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 25 publications
(30 reference statements)
3
81
0
4
Order By: Relevance
“…This is consistent with other studies that have shown that Lactobacillus is common in the bladders of adult women with and without lower urinary symptoms . It is not surprising that Lactobacillus predominates the urobiome of many adult women, given the beneficial role that Lactobacillus generally plays in other microbial niches, and the evidence that certain Lactobacillus species are associated with a lack of lower urinary tract symptoms and reduce the risk of post‐surgical UTI , . Injudicious antibiotic use may have collateral effects that reduce the Lactobacillus population, causing an unintended, subsequent vulnerability to the urobiome; a vulnerable urobiome may be more susceptible to invasion and/or overgrowth of opportunistic pathogens that are or may be associated with lower urinary tract symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with other studies that have shown that Lactobacillus is common in the bladders of adult women with and without lower urinary symptoms . It is not surprising that Lactobacillus predominates the urobiome of many adult women, given the beneficial role that Lactobacillus generally plays in other microbial niches, and the evidence that certain Lactobacillus species are associated with a lack of lower urinary tract symptoms and reduce the risk of post‐surgical UTI , . Injudicious antibiotic use may have collateral effects that reduce the Lactobacillus population, causing an unintended, subsequent vulnerability to the urobiome; a vulnerable urobiome may be more susceptible to invasion and/or overgrowth of opportunistic pathogens that are or may be associated with lower urinary tract symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The function of this urinary protein is not well understood, but it is associated with both cardiovascular and UT health and may influence overall UT host-microbiota interactions [317,318]. Trials investigating catheter-associated UTIs [319,320] already typically consider the unique microbiota profiles associated with these devices, but must now also consider the impact that cranberry materials may have on both initial patient UT microbiomes and on the development of both catheter biofilms and subsequent UTIs [63,321]. Clinical trials that investigate the concurrent use of cranberry materials and probiotics [313] must consider the possible prebiotic effects of cranberry oligosaccharides on both the existing microbiota and the provided probiotic organisms, as well as the possible colonization of the UT with the probiotic organisms [322,323].…”
Section: A New Paradigm For Uti Prevention With Cranberry Materialsmentioning
confidence: 99%
“…The discovery of the bladder microbiota (also known as the bladder urobiome) has led researchers to question how these microbes influence the health of the host. Studies have shown that altered bladder urobiome diversity is associated with urgency urinary incontinence (UUI) (4,8), urinary tract infection after instrumentation of the urinary tract (9,10), and is predictive of response to a common UUI drug (11). These studies collectively provide evidence that the bladder urobiome, while previously overlooked, is clinically relevant and warrants further investigation.…”
Section: Introductionmentioning
confidence: 97%